Communication Barriers and Adjustment Strategies of Foreign Students: A Case Study Analysis in A Private University - Ardhana, Mukhammad Rifky; Nurhayati, Iis Kurnia (eProceedings of Management, 2024)
The increasing demand for education has led to a rise in foreign students seeking global experiences. However, theyoften face communication barriers in their home universities, including Telkom University. A pre-research interviewat Telkom University exposed a gap between foreign and local students, with little interaction concerning campusorganization and events. This study aimed to identify these communication barriers and examine their adjustmentstrategies. The researcher used a qualitative method and case study methodology to analyze the issues faced by sixforeign students. The findings revealed five distinct communication barriers: assumptions of similarities, languagedifferences, non-verbal misinterpretations, preconceptions and stereotypes, and high anxiety. Factors contributing tothese barriers include cultural differences, media, personal beliefs/values, personal experiences, and historicalbackground. The students implemented a convergence strategy to address these barriers. The study highlights the needfor better communication between foreign and local students at Telkom University. Keywords-foreign students, communication gap, communication barriers, adjustment strategies.